Room Temperature Ferromagnetism of (Mn, Fe) Codoped ZnO Nanowires Synthesized by Chemical Vapor Deposition. (16th November 2012) - Chang, Yongqin; Wang, Pengwei; Sun, Qingling; Wang, Yongwei; Long, Yi
Abstract : (Mn, Fe) codoped ZnO nanowires were synthesized on silicon substrates in situ using a chemical vapor deposition method. The structure and property of the products were investigated by X-ray, electron microscopy, Raman, photoluminescence, and superconducting quantum interference device magnetometer. The doped nanowires are of pure wurtzite phase with single crystalline, and the elements distribute homogeneously in the doped nanowires. Photoluminescence spectrum of the doped nanowires is dominated by a deep-level emission with a negligible near-band-edge emission. The magnetic hysteresis curve with a coercive field of 35 Oe is clearly observed at 300 K, resulting from room-temperature ferromagnetic ordering in the (Mn, Fe) codoped ZnO nanowires, which has great potential applications for spintronics devices.